2020
DOI: 10.3389/frsc.2020.572572
|View full text |Cite
|
Sign up to set email alerts
|

Governing for Diversity: An Exploration of Practitioners' Urban Forest Preferences and Implications for Equitable Governance

Abstract: Urban forests are increasingly acknowledged as sources of multiple benefits and central to climate resilience and human well-being. Given these diverse and significant benefits, it is important to govern urban forests so as to ensure that all residents have equitable access and enjoyment. Understanding urban forest preferences, and including them in planning and management, is a key aspect of informed and contextually relevant urban forest governance. Although many studies have examined public urban forest pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…Environment professionals from both local governments and the private sector can also have granular insight into the ecology and seasonality of urban forests under their jurisdiction, and are closely aware of local constraints and demands on restoration practices. For instance, Sax, Manson & Nesbitt (2020) found that urban forest professionals in two large metropolitan areas put particular importance on urban forest accessibility (e.g. walking, public transport).…”
Section: Evidence Synthesis Of Urban and Rural Forest Restoration Res...mentioning
confidence: 99%
“…Environment professionals from both local governments and the private sector can also have granular insight into the ecology and seasonality of urban forests under their jurisdiction, and are closely aware of local constraints and demands on restoration practices. For instance, Sax, Manson & Nesbitt (2020) found that urban forest professionals in two large metropolitan areas put particular importance on urban forest accessibility (e.g. walking, public transport).…”
Section: Evidence Synthesis Of Urban and Rural Forest Restoration Res...mentioning
confidence: 99%
“…
against a backdrop of workforce demographic shifts and public perceptions of green space management (Silvera Seamans 2013;Ordóñez et al 2019;Sax et al 2020).Lack of clarity in urban forestry's professional identity has a long list of consequences. Competing professional organizations, disparate educational paths, and inconsistent job descriptions create challenges for those seeking careers and for development of a common body of knowledge for the profession (O'Herrin et al 2018a;O'Herrin et al 2018b).
…”
mentioning
confidence: 99%
“…against a backdrop of workforce demographic shifts and public perceptions of green space management (Silvera Seamans 2013;Ordóñez et al 2019;Sax et al 2020).…”
mentioning
confidence: 99%